(untitled) (Journal of Medical Sciences, 2023)
Background: Evaluation of the intern students have an essential role in assessing the efficiency of the provided education methods, clinical training, and the achievement of the intended learning outcomes of future graduates students. Aims: this study aimed to evaluate the internship program of undergraduate students and their ability to perform the all minor oral surgical procedures during the period allocated at Maxillofacial and Oral Surgery Department. The study also explored the confidence and level of satisfaction of students during the internship period. Material and methods: This study was conducted in Oral and Maxillofacial Department of Dental College, Sebha University from March to October 2021. There were 11 questions assessing various aspects of the undergraduate OMFS curriculum and internship period, including age, gender, and number of minor oral surgeries performed. Data was analysed by statistical package of social science (SPSS version 22). Result: A 30 questionnaires were completed, representing a response rate of 100% for the internship students. In general, the interns appeared very satisfied with their training experience 50%, 33.3% unsatisfied, and 16.7% still unsure. About half of the internships students expressed the three months enough to perform the all minor oral surgical procedures with 56.7%, whereas 33.3% expressed the two months, and 10% reported the one month was enough. Conclusion: This study revealed the internship period for the majority of undergraduate students is not sufficient to perform the all minor oral surgical procedures. They reported the high level of confidence and satisfaction during the internship period.